Differential organotin sensitivity in two Leucozonia species from a ship traffic area in southeastern Brazil - Costa, Mercia B.; Zamprogno, Gabriela C.; Pedruzzi, Felipe C.; De Morais, Leticia; Tognella, Monica M. P.; Godoi, Ana Flavia L.; Santos, Dayana M.; Marchi, Mary Rosa Rodrigues de [UNESP]; Fernandez, Marcos A. (Taylor & Francis As, 2014)
Tributyltin exposure is the primary cause of imposex development in gastropods, making them excellent bioindicators. The present research represents the first examination of butyltin (BT) contamination in surface sediments associated with imposex in Leucozonia nassa and L. ocellata in a harbour complex area in Espirito Santo, southeastern Brazil. The objectives of this study were to evaluate the organotin pollution in the area and to assess the sensitivity of both species to BT pollution through imposex development. Specimens were collected between 2007 and 2010 and the sediments were sampled in 2007. Imposex intensity was evaluated based on the percentage of imposexed females, the relative penis length index (RPLI) and the average value of the vas deferens sequence index (VDSI). BTs were analysed using gas chromatography equipped with a pulsed flame photometric detector (PFPD). The results demonstrated the occurrence of elevated concentrations of BTs in the sediment ranging from 383.7 to 7172.9 ng Sn g(-1), indicating a severe contamination of the area, which was confirmed by the biological monitoring results. Our findings also indicated that L. ocellata is a less sensitive species than L. nassa and that this differential sensitivity plays a key role in the distributions of the populations of both species in the studied area.
Keywords: Biological indicators; imposex; Leucozonia nassa; L; ocellata; organotins pollution